Challenging Capacity Building
XI, 269 p.
Keywords: Interrogates the idea of capacity building theoretically and explores the variety of meanings, constructions and practices of capacity building. This book examines capacity building in both developing and developed countries and takes the position that fragile communities are present in all societies.